PERFORMANCE OF SOMATIC EMBRYOGENESIS PROPAGATED COFFEE PLANTS UNDER DIFFERENT LEVELS OF SOIL WATER - Reis Almeida, Gustavo Rennó; Henrique Siqueira de Carvalho, Carlos; José Guimarães, Rubens (Coffee Science - ISSN 1984-3909, 2011)
Coffee micropropagation allows the multiplication of hybrids and segregating genotypes, and reduces from 30 to nearly 10 years, the time required to obtain new coffee cultivars. However, this technique is not yet ready for Coffea arabica L. large scale propagation and the field performance of plants produced through this process is not well known. This work aimed to study the behavior of plants propagated by indirect somatic embryogenesis. Two assays were carried out to compare vegetative propagated plants with seed derived plants. The first one studied radicular system morphology and plant response to water restrain and water excess. The second one was conducted in field conditions to evaluate the post-planting vegetative growth. In the greenhouse assay the vegetative propagated plants had higher vegetative growth than seed propagated plants in the following parameters: leaf and stem dry weight, plant height and number of orthotropic branches. There was no difference between the two propagation methods for the response to water stress. In the field trial the vegetative propagated plants showed higher vegetative growth during the first seven months for all the parameters evaluated. It was concluded that somatic embryogenesis propagated plants have better vegetative growth during the first seven months in the field and a similar response to plants obtained from seeds in water deficiency and water excess conditions.